Ayurveda Management of Diabetic Foot Ulcer - A Case Report: Life Sciences-Ayurveda - Asma; Dave, Omprakash; D Toshikhane, Hemant (International Journal of Life Science and Pharma Research, 2022)
Diabetic foot ulcer (DFU) is a major complication of Diabetes Mellitus (DM). DFU treatment principles consist of wound debridement, off-loading and education. Shastiupakrama (60 procedures) principles are explained for the management of Dustavrana(Chronic wound)which has been adopted in this study. The main objective of the study was to see the effect of Ayurvedic treatment in the management of DFU. A 46 years old male presented with the complaints of a non-healing ulcer at left great toe. The patient had a history of trauma with stone during working in the agricultural field and was treated conservatively with antibiotics and anti-inflammatory drugs by his family doctor. Patient was under regular medication for Diabetes Mellitus and Hypertension. On examination revealed an ulcer over the left great toe measuring 3 cm x 2cm with slough and blackish discolouration around the ankle region. Vasculopathy and neuropathy were evident by peripheral arterial palpation and Semmes-Weinstein Monofilament (SWM) test respectively. The case was effectively managed by both internal and external procedures with oral medications.The case was diagnosed as DFU as per contemporary science and Dustavrana(Chronic wound) as per Ayurveda based on laxana. The case was managed with treatment procedures like Chedana(Excision/Debridement), Prakshalana(Wound cleansing), Lepa(Topical application), Bandhana(Bandaging), Jalaukavacharana(Leech therapy), Manjistadi kshara basti(Medicated enema) and Shamanaoushadi(Internal medications). The ulcer took 3 months for complete healing with improvement in the patient’s quality of life to perform his routine activities. The adopted Ayurveda treatment has given promising results in the management of DFU. Further research in this aspect with Randomized Controlled Trial is essential.